2016
DOI: 10.1039/c6ra00382f
|View full text |Cite
|
Sign up to set email alerts
|

Solution combustion synthesis and physico-chemical properties of ultrafine CeO2 nanoparticles and their photocatalytic activity

Abstract: Solution combustion method was adopted for the preparation of ultrafine cerium oxide nanoparticles, which act as excellent photocatalysts for the degradation of dye from aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The intense peak at 630 cm −1 is assigned to Ce-O-Ce stretching vibration, confirming the formation of CeO 2 . 29 The CO and C-O bond vibrations are observed at around 884 and 1369 cm −1 , respectively. The band at 1616 cm −1 corresponds to the bending vibration of H 2 O absorbed from the atmosphere.…”
Section: Characterization Of the Catalystsmentioning
confidence: 98%
“…The intense peak at 630 cm −1 is assigned to Ce-O-Ce stretching vibration, confirming the formation of CeO 2 . 29 The CO and C-O bond vibrations are observed at around 884 and 1369 cm −1 , respectively. The band at 1616 cm −1 corresponds to the bending vibration of H 2 O absorbed from the atmosphere.…”
Section: Characterization Of the Catalystsmentioning
confidence: 98%
“…The growth process of nanostructures in the bottom-up approach can also be controlled with the assistance of reagents such as growth inhibitors, ligands and surfactants. The most popular bottom-up techniques are the wet chemical procedures such as the solution combustion synthesis (SCS) technique, [1][2][3][4][5][6][7] solution-based-hydrothermal and solvothermal methods, and polyol synthesis methods. However, the production of metal oxide nanostructures on a large scale through these techniques is currently limited due to the difficulties in controlling the properties of the bulky material and the utilizationin some casesof non-environmentally friendly chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, it has been established that ceria can be successfully used not only as a support for various active phases but it can also be involved as a promising active component for various reactions . Recently, cerium dioxide has been thoroughly studied for applications in advanced oxidation processes, e.g., photocatalytic oxidation or Fenton-like reactions. Many authors have reported that loading of ceria on the surface of semiconducting metal oxides is an efficient method to improve the photocatalytic performance of parent oxides. For instance, Zhu et al have documented that CeO 2 /ZnO composites displayed highly enhanced photocatalytic activity in Rhodamine B (RhB) degradation compared to pristine ZnO and CeO 2 .…”
Section: Introductionmentioning
confidence: 99%